Uma avaliação do Sistema Nacional de Avaliação da Educação Superior (SINAES) : medir o quê para quem, eis a questão! - Torres, Adriana Amadeu Garcia (2018)
The evaluation is a complex subject, which consists in judging the value and merit of evaluand (SCRIVEN, 1991). Higher Education in Brazil is evaluation by a national evaluation system (Sinaes) and this thesis aims to identify how and what is evaluated by Sinaes and to whom this evaluation process is intended, considering its cyclic process. Its relevance is to allow: the public power to rethink norms and procedures; the society makes its participation effective; the higher education institutions to maintain their identities; the students to broaden their view of the system; and the staff involved in the process works in gaps. So, in order to understand concepts, typologies and the evaluation process itself, three important publications were considered: Pfeifer (2012), Silva (2016) and Worthen et al. (2004). Besides that, the possible of ways to use it were found in: The evaluation of the quality of Davok (2006) and the Vector of Excellence (EWELL, 1984) and the Effectiveness Framework (KRAKOWER, 1985) of the National Center for the Management System of Higher Education (NCHEMS). For methodology required searching in different documents to develop a descriptive study capable of analyzing The Sinaes’s process and make recommendations and judgments. The analysis was performed in two ways: categorical, based on the six approach of the evaluation of Worthen et al. (2004); and of content; both with inferences and interpretations respecting the Bardin's proposal (2011). For that, was used a diversified data sources, constructing the research corpus with quantitative and qualitative data simultaneously. As a conclusion, there are two processes: proposed and implemented, via Sinaes, and many distortions were find, such as its beginning: in the plan it appears as being if by the institutional report; and in practice by the National Student Performance Exam (Enade). To identify what has been evaluated, two fronts must be considered: the visit and the Enade. In the visit, the 10 dimensions provided for in the Law that considered the HEI mission, its policies (teaching, management and personnel), interaction with society, infrastructure and financial sustainability are measured, albeit to a limited extent. The Enade measures the knowledge and skills of the student via exam and their perception on three institutional aspects: infrastructure, didactic-pedagogical organization and opportunities for extension of the training, by questionnaire. In relation to: for whom is measured. It is noted that, in practice, decisions are made by specific group based on legislation. Nevertheless, as a evaluation research, recommendations were made, and it was possible to propose a system of responsive evaluation that works a database for feeding all the actors involved. To do so, one must separate the processes of evaluation (judgments) and data collection (inputs), knowing that quality is not a single concept, but rather the result of a judgment.